RISK SECURITIZATION - Tobin, Gary (Assurances, 2001)
This paper is intended to shed some light on securitization, an evolving instrument for managing risk, specifically adressing those risks involving bond issues. This tool may be new to the insurance industry, but it has been around in the financial markets since the mid-seventies in the U.S., and is currently gaining acceptability in other countries.